Hair Cosmetics: An Overview - Gavazzoni Dias, Maria Fernanda Reis (Int J Trichology, 2015)
Hair cosmetics are an important tool that helps to increase patient's adhesion to alopecia and scalp treatments. This article reviews the formulations and the mode of action of hair cosmetics: Shampoos, conditioners, hair straightening products, hair dyes and henna; regarding their prescription and safetiness. The dermatologist's knowledge of hair care products, their use, and their possible side effects can extend to an understanding of cosmetic resources and help dermatologists to better treat hair and scalp conditions according to the diversity of hair types and ethnicity.